Threshold voltage decrease in a thermotropic nematic liquid crystal doped with graphene oxide flakes - Mrukiewicz, Mateusz; Kowiorski, Krystian; Perkowski, Paweł; Mazur, Rafał; Djas, Małgorzata (Beilstein Journal of Nanotechnology, 2019)
We report a threshold voltage decrease in a nematic liquid crystal compound, 4-cyano-4′-pentylbiphenyl (5CB), doped with graphene oxide (GO) flakes at a concentration of 0.05–0.3 wt %. The threshold voltage decrease was observed at the same concentration in electro-optic and dielectric spectroscopy measurements. The effect is related to the disrupted planar alignment due to the strong π–π stacking between the 5CB’s benzene rings and the graphene oxide’s structure. Additionally, we present the GO concentration dependence on the isotropic–nematic phase transition temperature, electric anisotropy, splay elastic constant, switch-on time, and switch-off time. The shape and dimensions of the GO flakes were studied using atomic force microscopy (AFM) and scanning electron microscopy (SEM). The influence of the GO concentration on the physical properties and switching process in the presence of the electric field was discussed.
Keywords: graphene oxide; liquid crystal; nematic phase; switching; threshold voltage